The transiton of nutritional status at first year medical students during e-classes - Nur Aini Djunet (World Nutrition Journal, 2022)
The second wave of COVID-19 pandemic is resulting in second lockdown at Indonesia. This results in classes to only be allowed in online. It may lead to obesogenic situation. Obesity is the first comorbid factor for COVID-19 complications dan mortality. We aim to investigate the nutritional status and its related factor at medical students after a year of e-classes.